Optimalisasi Nilai Cinta Budaya Lokal melalui Pendidikan Berbasis Budaya Bengkulu - Diki Ramadhani; Aprilia Srilestari; Ika Titian Junita; Nurul Robiyatul Abdabiah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service project at SD Negeri 16 Kota Bengkulu aims to enhance children's awareness of local culture. The primary objective is to cultivate a love for Bengkulu’s indigenous heritage through integrated cultural education. Utilizing the Asset-Based Community Development (ABCD) approach, the program leverages existing community strengths and cultural assets. Service-learning, field observation, and a descriptive qualitative methodology guide the design and implementation of a variety of cultural activities. Key activities include training in traditional dance and Dol music, the introduction of local games, exposure to Bengkulu folk songs, as well as the introduction of Batik Besurek and traditional foods. As part of the Pancasila Student Profile Strengthening Project (P5), the program also features the creation of Tabot miniatures and coloring wayang figures. Additionally, the program introduces the Kaganga script and raises awareness about cultural preservation. This comprehensive initiative is expected to significantly enhance students' appreciation and understanding of Bengkulu’s rich cultural heritage, contributing to the sustainable preservation of local traditions.